Local Understandings of Decent Work and the Legitimacy of Global Labour Standards: Insights from Garment Suppliers in Egypt and Jordan - Britta Holzberg (Journal of Business Ethics, 2023)
This paper contributes to the debates on the effectiveness and legitimacy of global labour standards. Theoretically, the paper integrates literature on labour standards in global production networks with cognitive framing and sensemaking literature to capture decent work understandings of suppliers and to theoretically underpin their relevance for the debates on the legitimacy and effectiveness of global labour standards. Empirically, the study explores cognitive decent work frames of garment suppliers and discusses them in reference to global decent work frames. A thematic analysis of semi-structured interviews with thirty owners and managers in Egypt and Jordan served to identify suppliers' decent work frames. Owners and managers dominantly framed decent work as a (paternalistic) family responsibility and as a business responsibility. Further notions that recurred across interviews were the framing of decent work as a human responsibility, religious (Islamic) responsibility, philanthropic responsibility, and regulatory responsibility. The findings show that supplier frames partly go beyond, partly undermine, and partly accord with global conceptualisations of decent work. They imply the need to strengthen and better communicate the human rights orientation of global labour standards and to give local social partners the autonomy to supplement and specify standards according to their context-specific needs. Global regulations otherwise risk crowding out informal, locally specific decent work practices that benefit workers in GPNs.
Keywords: 300; Decent work; Global garment supply chain; Supplier agency; Corporate social responsibility; Framing and sensemaking; Middle East and Northern Africa